Загальна технологія системи технічного зору в прикладах і задачах - Кравченко, Олександр Сергійович (Національний технічний університет "Харківський політехнічний інститут", 2019)
Розглянуто лазерну систему технічного зору для слідкування за зварювальним швом. Описане математичне обґрунтування застосованого алгоритму. Алгоритм використовує метод екстремального значення, що полягає у виборі максимального значення на поперечному перерізі лазерної лінії в якості центра. Для вдосконалення точності алгоритму застосовується метод згортання матриці.

This paper introduces positions of system analysis concept on shortening of time needed for robot’s algorithms and software successful development with taking into consideration the mechanic, electronic and technological circumstances. The means of the increasing of the robot’s work reliability are also considered. The work is based on the experience of creation of great number of control systems and software for a wide number of the robots, different by appointment and the constructive scheme. The laser system of technical vision for tracking the weld is considered. The mathematical justification of the applied algorithm is described. The algorithm uses the extreme value method, which is to select the maximum value at the cross section of the laser line as the center. To improve the accuracy of the algorithm, the method of minimizing the matrix is used.
General technology of technical vision system in examples and tasks
Keywords: інтелектуальна власність; процес роботи; тріангуляція; intellectual property; work process; triangulation